THE EFFECT OF MARKET ORIENTATION ON THE MARKETING PERFORMANCE OF MSMES WITH SUPPLY CHAIN MANAGEMENT STRATEGIES AS A MEDIATION VARIABLE (STUDY ON MSMES IN MAKASSAR CITY) - Nurul Fadilah Aswar; Hasmyati; Nur Indah Atifah Anwar (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This study aims to evaluate the application of market orientation to marketing performance, taking into account the SCM strategy as an intervening variable in small and Medium Enterprises (SMEs) in Makassar. Data collection was conducted by distributing questionnaires of 70 copies to managers or owners of SMEs in Makassar. The collected Data were analyzed using structural Equation Model (SEM) analysis method using Smart Pls program. The results found several significant things, namely: 1) there is a significant positive influence between market orientation and marketing performance. 2) there is a significant positive influence between market orientation and SCM strategy. 3) there is a significant positive influence between SCM strategy and market performance. 4) there is a positive and significant influence between market orientation and marketing performance of the company through the practice of SCM on SMEs in the city of Makassar.